(3TQM dCdajI GHf eGdcs - (3eLghds
(3ChdgG (B:s
(3HMK GdcdGe heG jJCda efg , cdGefG daX eajO cGSJbe (B.. (3GdcdGe YfO GdfMhjjf gh GddaX GdOGd Ydi eYfi jMSf GdSchJ Ydjg hgPG (B... (3eajO cGSJbe cCfg bGd GdcdGe daX eajO aGFOI JGeI (B...s
(3BNQgG (B:s
.. (3dCfg CNa ef GdUaI acCf CMeO GdeKbd heKd Jbhi HeYfi GdeKd hGdaJhi hGdHbhi hGdKfhi HeYfi GdaJhGj hGdHbjG hGdTfjG hbhdg ZGdHG GMJQGR ef fMh bhdge ddQGFMI (B...s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3GdfMhs